A novel and efficient cogeneration system of waste heat recovery integrated carbon capture and dehumidification for coal-fired power plants. (1st March 2022) - Su, Zixiang; Yang, Liu
Graphical abstract: Highlights: A multistage and multipurpose cogeneration system is proposed. The power and thermal efficiency of power plant increase by 13.34% and 5.74%. Capturing carbon dioxide as subsystem medium is conducive to emission reduction. Moisture in coal or exhaust is eliminated by dehumidification to enhance performance. Abstract: Presently, coal-fired power plants are facing the situation of low energy utilization and high pollution emission, to achieve the goal of energy conservation and emission reduction, the implementation of waste heat recovery is imperative. Therefore, a novel and efficient cogeneration system of waste heat recovery integrated carbon capture and dehumidification, is developed in this investigation. The mathematical model of the system is first established and verified, and the performance comparison of high-temperature cycle, cooperativity discussion of cascade power generation system, sensitivity analysis of working parameters, and positive effect of dehumidification system, are then carried out. After mastering the change rule, the three-objective optimization is performed with the objectives of maximum power generation, minimum payback time, and maximum carbon capture capacity. Eventually, the benefit of the coal-fired power plant and cogeneration system is comprehensively evaluated. The numerical results display that the power generation and thermal efficiency of the coal-fired power plant are increased by 13.34% and 5.74%, under maximum working condition, with additional cooling capacity, moisture removal rate, and carbon capture capacity of 135.58 MW, 15.69 g/kg, and 130.99 kg/s, can recover capex within 5.36 years. It conforms to the concept of green and efficient development, complies with the requirements of carbon neutralization, and lays a theoretical foundation for the promotion of cogeneration system in coal-fired power plants.